Próba charakterystyki warunków rozwoju pradziejowej gospodarki hodowlanej w północnej części Borów Tucholskich - Grzelakowska, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1989)
A certain departure from the model of economic development generally accepted in the rest of Polish territories is seen in the development of ancient and early mediaeval economy of the people dwelling in the northern parts of Tuchola Forests. Untill the end of the early bronze age an extensive economy of mesolythic character and since then the animal breeding dominated there. The land cultivation, although it has been confirmed by the presence of single grains of corn in pollen analysis spectrum since the younger Atlantic period was probably the secondary economic activity of the people till the Roman period. Only in early Middle Ages (about the XIIIth century) one can tell about the increased range of agriculture. It is likely that local younger mesolythic communities got to know the animal breeding due to contacts with population of culture of funnel-beaker culture. It seems that beginning with the younger Atlantic period the animal breeding initially accompanied other branches of economy of mesolythic character but with time it became dominating among other farming activities. It seems to reach its climax during Łużyce – Pomeranian period(from the end of the IVth period of the bronze age till the mid Laten period) but in successive periods the animal breeding may have played an important role in economy of the local people. Environmental conditions which on one hand hindered the development of agriculture on and on the other hand were conducive to extensive methods of gaining food in sufficient amount for maintaining groups of people dwelling in the discussed period in the northern part of Tuchola Forests were favourable for such a model of economic development.